2010
DOI: 10.4028/www.scientific.net/msf.654-656.926
|View full text |Cite
|
Sign up to set email alerts
|

Dispersoid Phases in 6xxx Series Aluminium Alloys

Abstract: In high strength AlMgSi alloys additions of Mn and Cr lead to the formation of dispersoid phases whose primary functions are to improve fracture toughness and control grain structure. Whether or not dispersoid phases form during heating to the homogenisation temperature and which dispersoid forms is strongly dependent on the alloy composition. By correlating dispersoid features after different homogenisation heat treatments to TEM investigations into the crystal structure, it is proposed that the crystal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Subsequently the alloy was extruded, solution treated at 550 C for 1 h, quenched with forced air and cold water, respectively, and aged (8 h at 175 C). The dispersoids have previously been characterised 13) and it was found that as the homogenization temperature and time increased the dispersoid size also increased, but the composition and crystal structure of the dispersoids changed depending on the dispersoid size from sc for dispersoids with a length smaller than 200 nm to bcc for large dispersoids with a length exceeding 200 nm. Despite this the quench sensitivity was again linearly related to the dispersoid density.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently the alloy was extruded, solution treated at 550 C for 1 h, quenched with forced air and cold water, respectively, and aged (8 h at 175 C). The dispersoids have previously been characterised 13) and it was found that as the homogenization temperature and time increased the dispersoid size also increased, but the composition and crystal structure of the dispersoids changed depending on the dispersoid size from sc for dispersoids with a length smaller than 200 nm to bcc for large dispersoids with a length exceeding 200 nm. Despite this the quench sensitivity was again linearly related to the dispersoid density.…”
Section: Discussionmentioning
confidence: 99%
“…Insoluble or undissolved intermetallic particles and dispersoids, such as ß-Al 5 FeSi, α-Al 15 (FeMn) 3 Si and α-Al 12 (Fe,Mn) 3 Si, which form during solidification or homogenisation, can be present in Al-Mg-Si type alloys with Mn and Fe additions and impurities [67,79,80,81,82,83,84]. The SEM micrograph in Fig.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The black particles were too small to be assayed accurately with this tech nique but the results indicated that they were rich in Mg and Si and were in an approximate 2:lMg-Si ratio. Based on these results, the literature indicates that these particles are most likely Fe3SiAl12 (gray) and Mg2Si (black) in both alloys [47][48][49], Some differences between the two as-polished microstructures were observed, the most prominent being in the size distributions of the microconstituent particles. The results of a particle analysis conducted on the two (276 x 219) /mi areas in Fig.…”
Section: Metallographymentioning
confidence: 90%